Differential equations and their applications - Braun, Martin (Springer-Verlag, 1993)
Ch. 1. First-order differential equations -- Ch. 2. Second-order linear differential equations -- Ch. 3. Systems of differential equations -- Ch. 4. Qualitative theory of differential equations -- Ch. 5. Separation of variables and Fourier series -- Ch. 6. Sturm-Liouville boundary value problems -- Appendix A: Some simple facts concerning functions of several variables -- Appendix B: Sequences and series -- Appendix C: C Programs.; Includes index; Includes index.